Classificational and Theoretical Execution Misconceptions: Classification of Misconceptions Based on Students Concepts in Plane Geometry - Fuat Fuat; Keto Susanto; Firda Qurrotul Aini (Journal of Education and Learning Mathematics Research (JELMaR), 2020)
Misconception is a mismatch of students’ conceptions with concepts agreed upon by experts. Misconception is a problem that often occurs in the world of education, especially in mathematics in the matter of plane geometry. This type of research is a descriptive qualitative research that aims to describe the types of misconceptions and causes of misconceptions experienced by students on the subject of plane geometry. The results showed that there were two types of misconceptions experienced by students, namely classificational execution misconceptions, and theoretical execution misconceptions. Misconception of classificational execution is the mismatch of students' conceptions when classifying a plane geometry with a concept agreed upon by experts; and the theoretical execution misconception is a mismatch between students' conceptions of definition, properties and elements of planes geometry. The causes of misconception are students 'preconceptions, students' abilities, textbooks, and teacher teaching methods.